Clinical Impact of Dyspnea after Ticagrelor Treatment and the Effect of Switching to Clopidogrel in Patients with Myocardial Infarction - Kim, Sang Hyun; Shin, Sanghoon; Choo, Eun Ho; Choi, Ik Jun; Lim, Sungmin; Moon, Donggyu; Kim, Chan Joon; Park, Mahn-Won; Kim, Min Chul; Hwang, Byung-Hee; Lee, Kwan Yong; Choi, Yun Seok; Kim, Hee-Yeol; Yoo, Ki-Dong; Jeon, Doo Soo; Ahn, Youngkeun; Chang, Kiyuk; on behalf of the TALOS-AMI investigators (Thrombosis and Haemostasis, 2024)
Background Dyspnea is frequent during ticagrelor-based dual antiplatelet therapy (DAPT) for acute myocardial infarction (AMI). However, its clinical characteristics or management strategy remains uncertain.Methods The study assessed 2,617 AMI patients from the Ticagrelor versus Clopidogrel in Stabilized Patients with AMI (TALOS-AMI) trial. Dyspnea during 1-month ticagrelor-based DAPT and following DAPT strategies with continued ticagrelor or de-escalation to clopidogrel from 1 to 12 months were evaluated for drug adherence, subsequent dyspnea, major adverse cardiovascular events (MACE), and bleeding events.Results Dyspnea was reported by 538 patients (20.6%) during 1 month of ticagrelor-based DAPT. Adherence to allocated DAPT over the study period was lower in the continued ticagrelor arm than the de-escalation to clopidogrel, particularly among the dyspneic population (81.1% vs. 91.5%, p < 0.001). Among ticagrelor-treated patients with dyspnea, those switched to clopidogrel at 1 month had a lower frequency of dyspnea at 3 months (34.3% vs. 51.7%, p < 0.001) and 6 months (25.5% vs. 38.4%, p = 0.002) than those continued with ticagrelor. In patients with dyspnea in their 1-month ticagrelor-based DAPT, de-escalation was not associated with increased MACE (1.3% vs. 3.9%, hazard ratio [HR]: 0.31, 95% confidence interval [CI]: 0.08–1.11, p = 0.07) or clinically relevant bleeding (3.2% vs. 6.2%, HR: 0.51, 95% CI: 0.22–1.19, p = 0.12) at 1 year.Conclusion Dyspnea is a common side effect among ticagrelor-based DAPTs in AMI patients. Switching from ticagrelor to clopidogrel after 1 month in AMI patients may provide a reasonable option to alleviate subsequent dyspnea in ticagrelor-relevant dyspneic patients, without increasing the risk of ischemic events (NCT02018055).
Keywords: dyspnea; acute coronary syndrome; ticagrelor; clopidogrel